Skrining Fitokimia dan Uji Kualitatif Aktivitas Antioksidan Ekstrak Etanol Daun Ketepeng Cina (Cassia Alata L) dengan Metode DPPH - Husen Ernawati; Supardi Rifani Hutami; Mantali M. Fathurrachman (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Cassia alata L or generally knowles as Chinese leaves contain phytochemical compounds, one of which is flavonoids which have the potential as antioxidants, antioxidants can be used to prevent diseases with oxidative stress. The purpose of this study was to determine the content of phytochemical screening and qualitative testing of antioxidant activity ethanol ekstract of Chinese leaves (Cassia alata L) using the DPPH method. This study is a qualitative study with an extraction process using the maceration method with 96% ethanol solvent. Phytochemical screening and antioxidant activity testing were carried out by adding specific reagents. The results of phytochemical screening and antioxidant activity testing of Chinese leaves (cassia alata L) ekstract contain bioactive compounds such as flavonoids, saponins, tannins and antioxidant activity testing with DPPH reagents showed that Chinese leaves (cassia alata L) extract has antioxidant activity which is indicated by a change of the color from purple to yellow. From the results obtained, it can be concluded that the flavonoid compound content in Chinese leaves (cassia alata L) extract can potentially act as an antioxidant.